Kindergarten years learning through play - Barrett, Joan.; Elementary Teachers' Federation of Ontario ([Ontario Elementary Teachers' Federation of Ontario], 2000)
This resource document will help teachers plan for developmentally appropriate, play-based programs as supported by the most recent research and The Kindergarten Program (Ontario Ministry of Education And Training 1998). Written by Junior and Senior Kindergarten teachers, this document highlights the learning environment of the kindergarten classroom.
"Prepared for the Elementary Teachers' Federation of Ontario".
Keywords: Kindergarten -- Activity programs; Kindergarten -- Activity programs -- Ontario; Kindergarten -- Ontario -- Curricula; Curriculum planning -- Ontario; Play